Influences of exposure to 915-MHz radiofrequency identification signals on serotonin metabolites in rats: a pilot study. (1st February 2021) - Kim, Hye Sun; Paik, Man-Jeong; Seo, Chan; Choi, Hyung Do; Pack, Jeong-Ki; Kim, Nam; Ahn, Young Hwan
Abstract: Purpose: The influences of radiofrequency electromagnetic exposure on animal health, particularly on serotonin metabolism, are not well-elucidated. In this in vivo study, we studied the influences of exposure to radiofrequency identification (RFID) signals on serotonin metabolism. Materials and methods: Twenty-two male Sprague–Dawley rats were assigned to sham ( n = 10) and RFID-exposed ( n = 12) groups. Rats in the RFID-exposed group were exposed to RFID signals at an average whole-body specific absorption rate of 2 W/kg for 8 h/day, 5 days/week for 2 weeks. Before and after RFID exposure, 24-h urine was collected from each rat. Urinary tryptophan, 5-hydroxytryptophan, serotonin, 5-hydroxyindoleacetic acid, and 5-methoxyindole-3-acetic acid concentrations were examined using gas chromatography-mass spectrometry, and changes in the patterns of values were compared between the two groups. Results: Urinary levels of serotonin decreased by 20% ( p = .041, Student's t -test) and 40% ( p = .024, Student's t -test) in both the sham and RFID-exposed groups, respectively. The level of 5-methoxyindole-3-acetic acid decreased by 30% in the RFID-exposed group ( p = .039, Student's t -test). Conclusion: Our results indicate that exposure to RFID signals at a specific absorption rate of 2 W/kg is sufficient to alter serotonin metabolism in rats regardless of whether the exposure level is considered biohazardous.